Effect of Hylocereus polyrhizus Extract to VEGF and TGF-β1 Level in Acute Wound Healing of Wistar Rats - Tahir, Takdir; Bakri, Syakib; Patellongi, Ilhamjaya; Aman, Makbul; Miskad, Upik; Yunis, Maryunis; Yusuf, Saldy (Jordan Journal of Pharmaceutical Sciences, 2021)
This study aims to identify the effect of Hylocereus polyrhizus on the level of VEGFs and TGF-β1 in acute Wistar rat wounds. Male Albino Wistar rats (n = 54) whose (250-350 g) were divided into 3 groups (negative control, positive control, and Hylocereus polyrhizus). The animals were wounded at right and left dorsal back with an 8 mm punch biopsy. Hylocereus polyrhizus 7.5% topical cream was applied on the wound surface using a cotton bud. The VEGF and TGF-β1 were evaluated with ELISA on the 3rd, 7th, and 14th days. Analyzed using independent t-test and paired t-test (SPSS 21, Chicago Inc.). The Hylocereus polyrhizus group had higher level of VEGF and TGF-β1 compared to positive control (p = 0.011; r = -0.584) and (p = 0.000; r = 0.888), respectively, on the 14th day. It was found that there was an upward trend between the TGFβ-1 level and the tissue granulation’s score (p: 0.051 and r: -0.466) as well as TGFβ-1 levels with epithelialization score (p: 0.001 and r: 0.708) in the Hylocereus polyrhizus topical group. This study has shown that Hylocereus polyrhizus can accelerate wound healing during both the inflammation and proliferation phase.